Novas técnicas de arranjos de semeadura na cultura da soja - Carvalho, Leidiane Coelho [UNESP]; Bueno, Regiane Cristina Oliveira de Freitas [UNESP]; Carvalho, Marina Mouzinho [UNESP]; Favoreto, Ana Laura [UNESP]; Godoy, Ana Flávia [UNESP] (My University, 2013)
Several factors induce soybean growers to seek new alternatives to increase productivity, in order to always surpass the previous harvest. In an attempt to meet this need in order to become more competitive, new technologies emerge. Currently, for example, the plantation system crossover, double row and dense, gaining media coverage and among researchers, aroused interest in research institutions. To date, there are still few studies with a scientific concrete, quantifies the real benefit of these cropping systems. The technique consists of sowing planting crossed the same area twice at right angles, forming checkerboard. In the planting row and the denser planting increases the number of plants per hectare, but the way they are arranged is what differentiates. Apparently these systems imply some issues, such as the use of inputs that the principle would double, as the plant population in the area will be changed, so possibly the incidence of insect pests and pathogens increase in these cropping systems. The purpose of this literature review is to provide updated information on technology, benefit from it, as it is being used and the research being conducted to provide scientific basis for soybean producer.

Vários fatores induzem os sojicultores a buscarem novas alternativas para aumentar a produtividade, com intuito de sempre superar a safra anterior. Na tentativa de atender essa necessidade, a fim de tornar-se mais competitivo, surgem novas tecnologias. Atualmente, por exemplo, o sistema de plantio cruzado, fileira dupla e adensado, vem ganhando repercussão na mídia e entre os pesquisadores, despertado interesse nas instituições de pesquisa. Até o momento, ainda são escassos os estudos com embasamento científico concretos, que quantifique o real benefício destes sistemas de semeadura. A técnica do plantio cruzado consiste em semear a mesma área duas vezes em sentido perpendicular, formando quadriculado. No plantio de fileira e no plantio adensado aumenta-se o número de plantas por hectare, porém a forma como estão dispostas é o que diferencia. Aparentemente esses sistemas implicam em algumas questões, como utilização de insumos que a princípio dobraria, visto que a população de plantas na área será alterada, assim possivelmente a incidência de insetos-pragas e de agentes patogênicos aumentaria nestes sistemas de semeadura. A finalidade desta revisão bibliográfica será fornecer informação atualizada sobre tecnologias, benefício da mesma, como está sendo utilizada e as pesquisas que estão sendo realizadas, para fornecer embasamentos científicos para o sojicultor.
New techniques of arrangements for seeding in soybean crop abstract
Keywords: Productivity; Cropping systems; Population density; Produtividade; Sistemas de semeadura; Densidade populacional